2021
DOI: 10.3390/su13052508
|View full text |Cite
|
Sign up to set email alerts
|

The B Corp Movement: A Systematic Literature Review

Abstract: This work develops a systematic literature review on the B Corp movement. Fifty articles were identified in the Web of Science and Scopus databases until 2020. Results show that it is an incipient field with great potential. There are two topics repeatedly addressed in the analyzed publications: the motivations of companies to be certified, and the economic and social effects that occur after certification. Sustainability is currently the reference journal in the field, since it has published a total of five a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 71 publications
(194 reference statements)
0
57
0
3
Order By: Relevance
“…Companies are key actors in promoting SD (Diez-Busto et al, 2021). There is considerable research into understanding how business works and stakeholders' value is created.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies are key actors in promoting SD (Diez-Busto et al, 2021). There is considerable research into understanding how business works and stakeholders' value is created.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They conclude that more recent research emphasizes B Corp studies through various lenses, such as CSR and sustainable business models. In another SLR on the B Corp movement, encompassing 50 scientific articles published until 2020, Diez‐Busto et al (2021) identified some of companies' motivations to be B Corp certified and the economic and social effects of certification to be the primary research topics. The results indicate some inconsistencies between different studies, suggesting the need to harmonize research criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike a traditional narrative literature review, our approach produces results that are scientific and transparent, which helps to limit research bias due to the subjectivity of the researcher conducting the review process. Our work overcomes the limitations of existing literature review on B Corps (i.e., Diez-Busto et al, 2021), which, at present, offers only a partial analysis of the body of the literature in this field.…”
Section: Methodsmentioning
confidence: 91%
“…In particular, CBCs, especially smaller and/or younger ones, may have difficulties in this endeavor as a consequence of the lack of economic resources, business knowledge and/or external environment support [24].…”
Section: Struggles Faced By Cbcsmentioning
confidence: 99%
“…Additionally, fiscal help could be highly beneficial for CBCs given that many of them achieve their impacts directly through the selling of their products [24], which many times leads them to reduce their margins in order to make their offer more accessible [5].…”
Section: Government Policies: Taxes and Bureaucracymentioning
confidence: 99%